Erzin’in Kuruluşu, Gelişmesi ve Fonksiyonel Özellikleri - Boyraz, Zeki (Afyon Kocatepe Üniversitesi, 2007)
Erzin Akdeniz Bölgesinin Adana bölümünde, 25879 nüfuslu bir kasabadır. Hatay iline bağlı bir ilçe merkezi olan Erzin;14-15. yüzyılda Dörtyol Ovasının kuzeydoğusunda kurulmuştur. Bu araştırmada, Erzin kasabasının kuruluş alanı incelenerek, kuruluş tarihinden şimdiye kadarki alansal gelişim aşamaları belirlenmeye çalışılmıştır. Ayrıca Erzin’in geçmişteki ve günümüzdeki fonksiyonel özellikleri belgeler ışığında incelenmeye özen gösterilmiştir.

Erzin is one of Hatay’s towns located in Adana part of Mediterranean region and has population of 25879. It was established in the North- east of Dörtyol plain in the 14th and 1501 centuries. In this study, the establishment place of Erzin is examined. The development stages of Erzin from the beginning date up to present time are tried to be specifıed. In addition, its functional features not only in the past but also at present are shown with documents.
The Establishment, and Development of the Town of Erzin and Its Functional Features
Keywords: Erzin; Kasaba; Şehirsel Fonksiyonlar; Hatay